Architecture and space - Schirmbeck, Egon; Boettger, Till (Berlin DOM Publishers, 2011)
Outstanding solutions and unusual approaches to architectural challenges are therefore a valuable source of inspiration for designers to draw on. This book introduces thirty special concepts by significant 20th century architects. The individual studies are the result of an extensive survey conducted at the Bauhaus University in Weimar and covers designs by pioneers of modernism such as Le Corbusier and Frank Lloyd Wright, as well as contemporary architects, including Zaha Hadid.
Keywords: ARCHITECTURE GENERAL (AR-GEN)